(untitled) (Baghdad Science Journal, 2009)
Brucella melitensis isolates were obtained from human infections , and milk which obtained from aborted sheep at Mosul city vicinity . One isolate from each source was used in carrying out this study. Brucella liquid culture was added to sheep milk at 2.5 % for treatments . To first treatment 2 % of yoghurt starter ( Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus salivarius subsp. thermophilus ( 1: 1 ) ) . Second treatment was carried out without addition of yoghurt starter but the pH was lowered using lactic acid in pattern similar to first treatment . Third treatment was similar to the first treatment but contained buffer to alleviate the reduction in pH , which reduced to 6.1 in comparison to 4.9 of the first treatment . Results showed that there was a parallel reduction in pH value and Brucella number with correlation coefficient of ( r = -0.945 ) for human isolate , and ( r = -0.974 ) for milk isolate . Addition of lactic acid with out starter led to decrease the killing of Brucella as the resulted numbers were three folds higher than the corresponding treatment of human isolate ( 67.7 % killing ) and 1.6 times for milk isolate ( 37.5 % killing ) . Addition of buffer reduced the killing percentage of Brucella and the viable count of Brusella , and it was 5.8 times the corresponding first treatment (17.20% killing ), while the milk isolates was 7 times (13.5 % killing ) at the end of fermentation process .